Crescent‐Shaped Electron Distributions at the Nonreconnecting Magnetopause: Magnetospheric Multiscale Observations. Issue 6 (19th March 2019) - Tang, B.‐B.; Li, W. Y.; Graham, D. B.; Rager, A. C.; Wang, C.; Khotyaintsev, Yu. V.; Lavraud, B.; Hasegawa, H.; Zhang, Y.‐C.; Dai, L.; Giles, B. L.; Dorelli, J. C.; et al.
Abstract: Crescent‐shaped electron distributions perpendicular to the magnetic field are an important indicator of the electron diffusion region in magnetic reconnection. They can be formed by the electron finite gyroradius effect at plasma boundaries or by demagnetized electron motion. In this study, we present Magnetospheric Multiscale mission observations of electron crescents at the flank magnetopause on 20 September 2017, where reconnection signatures are not observed. These agyrotropic electron distributions are generated by electron gyromotion at the thin electron‐scale magnetic boundaries of a magnetic minimum after magnetic curvature scattering. The variation of their angular range in the perpendicular plane is in good agreement with predictions. Upper hybrid waves are observed to accompany the electron crescents at all four Magnetospheric Multiscale spacecraft as a result of the beam‐plasma instability associated with these agyrotropic electron distributions. This study suggests electron crescents can be more frequently formed at the magnetopause. Plain Language Summary: In this study, we present Magnetospheric Multiscale mission observations of electron crescents at the flank magnetopause and these agyrotropic electron distributions are formed at thin electron‐scale magnetic boundaries after electron pitch angle scattering by the curved magnetic field. These results suggest that agyrotropic electron distributions can be more frequently formed at the magnetopause: (1) magnetic reconnection is not necessary, although electron crescents are taken as one of the observational signatures of the electron diffusion region, and (2) agyrotropic electron distributions can cover a large local time range to the flank magnetopause. In addition, upper hybrid waves accompanied with the electron crescents are observed as a result of the beam‐plasma interaction associated with these agyrotropic electron distributions. This suggests that high‐frequency waves play a role in electron dynamics through wave‐particle interactions. Key Points: Agyrotropic electron crescents are found in a nonreconnecting current sheet at the flank magnetopause These electron distributions are generated by finite gyroradius effect after magnetic curvature scattering The observed electron crescents can excite upper hybrid waves